An Improved 3D Localization Algorithm for the Wireless Sensor Network - Yan Xu; Yi Zhuang; Jing-jing Gu (International Journal of Distributed Sensor Networks)
Location information is crucial in the wireless sensor network. The nodes in wireless sensor networks are often deployed in the three-dimensional scenario. Therefore, the three-dimensional localization algorithm has become hot in wireless sensor networks. However, existing 3D localization algorithms have shortcomings, such as high complexity, low positioning accuracy, and great energy consumption. Aiming at the existing problems of the current 3D localization algorithms, an improved 3D localization algorithm based on Degree of Coplanarity (3D-IDCP) is proposed. The concept of coplanarity is added into the traditional DV-Distance algorithm to reduce the positioning error caused by anchor nodes which are coplanar. Those unknown nodes which have been located are promoted to assistant anchor nodes to improve the positioning coverage. The simulation results show that the proposed method is accurate in positioning and can enhance the positioning coverage.